PENGARUH KEPUASAN KERJA DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN DIVISI KAPAL NIAGA PT X - Moch Rafiq Asya'ari; Rini Nurahaju; Tri Budi Marwanto (Fakultas Psikologi Universitas Hang Tuah, 2023)
Abstract. Companies need support of employees who are reliable and and demonstrate commitment to their work so that the company's vision and mission can be achieved. One way to achieve this is by willingly doing tasks beyond their responsibility for the progress of the company (extra role) or commonly known as organizational citizenship behavior. The purpose of this study was to determine the effect of job satisfaction and organizational culture on organizational citizenship behavior in employees of the Commercial Ship Division of PT PAL Indonesia (Persero). A total of 152 employees were selected as respondents using a non-probability sampling technique with accidental sampling method. The results showed that there was a simultaneous effect of job satisfaction and organizational culture variables on organizational citizenship behavior variables, with an effect size of 98.6%.